(untitled) (Development Service Industry Management, 2024)
The article focuses on issues of the theoretical and methodological foundations of the functioning and development of the labor market. The socio-economic role and specifics of the functioning of the market of agricultural products are defined. The purpose of the article is to generalize the theoretical and methodological principles of the socio-economic role and features of the functioning and development of the market of agricultural products. On the basis of the generalization of the theoretical and methodological principles of the research of the market of agricultural products, it was established that a complex multi-level mechanism mediating the processes and relationships that arise during the production, distribution, exchange and consumption of agricultural products should be laid as a basis for its essential and substantive characteristics, as well as ensuring harmonization (through institutions such as supply and demand, price, etc.) of the socio-economic interests of agricultural producers, logistics and trade intermediaries, consumers (final and intermediate consumption) of agricultural products, elements of the market infrastructure and the state. At the same time, the market of agricultural products has specific features, the consideration of which, on the one hand, allows us to clarify the theoretical and methodological principles, and, on the other hand, to develop applied mechanisms of the policy of regulating its development. The specified features are mainly due to the specifics of the conditions and factors of agricultural production (supply side), as well as the parameters of purchase and consumption of agricultural products (demand side) and provide specific characteristics of the functioning of the analyzed market in terms of competition, market infrastructure, its internal integration processes, regulatory policy, implementation of social roles and tasks.